Biomass-Derived 2,3-Butanediol and Its Application in Biofuels Production - Bai, Yuchen; Feng, Huiya; Liu, Nan; Zhao, Xuebing (Energies (Basel), 2023)
2,3-butanediol (2,3-BDO) is an important biomass-derived platform chemical with various applications. Currently, the biological conversion of renewable carbon sources with bacteria or yeasts is a sustainable way to produce 2,3-BDO. Various carbon sources including glucose, glycerol, molasses and lignocellulose hydrolysate have been used for 2,3-BDO production, and the 2,3-BDO concentration in the fermentation broth can be higher than 150 g/L by optimizing the operating parameters with fed-batch operations. Various derivatives can be produced from 2,3-BDO, including isobutyraldehyde, 1,3-butadiene, methyl ethyl ketone (MEK), diacetyl, etc.; among these, there is a large market demand for MEK and 1,3-butadiene each year. Some of the derivatives can be used as fuel additives or to produce biofuels. Generally, there are three ways to produce hydrocarbon fuels from 2,3-BDO, which are via the steps of dehydration, carbon chain extension, and hydrogenation (or hydrodeoxygenation), with MEK or 1,3-butadiene as the intermediates. C8–C16 alkanes can be produced by these routes, which can be potentially used as bio-jet fuels. This review article focuses on the microbial production of 2,3-BDO, the biomass feedstock used for fermentation, the recovery of 2,3-BDO from the fermentation broth as well as the downstream derivative products and their potential application in bio-jet fuel production. It was concluded that 2,3-BDO is a promising biomass-derived product, but its production and application in the biofuel field is still facing the problem of high production cost. Future work is recommended to develop more efficient processes to increase the 2,3-BDO yield and more advanced technologies to produce hydrocarbon fuels.